Turismo e paisagem cultural: para pensar o transfronteiriço - Costa, Luciana de Castro Neves (My University, 2014)
The analysis developed in this research origins from the perception of the need of more profound studies related to brazilian border areas, regarding tourism, specially in their cultural and symbolic dimension. Beyond the political issues and meaning constructions about frontiers, influenced by the globalization process, there s been emerging news conceptions about heritage, broadening its understanding and diversifying its instruments of protection. In the present case, the study focus on the new category of heritage Brazilian Cultural Landscape, that emphasizes the relation and mutual interdependence between the human action and the physical characteristics of space on the specific configuration of determined landscape. In these terms, the present investigation presents as main objective to analyse the possibility of the new proposition of heritage Brazilian Cultural Landscape comprehend the complexity of the boundary condition that manifests in the relationships established in the borderlands, specifically in the border area of Brazil and Uruguai. The research is developed in the cities of Jaguarão (State of Rio Grande do Sul, Brazil) and Rio Branco (Department of Cerro Largo, Uruguai), searching to understand the cultural dimension in an ambiguous space of separation-contact condicioned by the Jaguarão river and the International Bridge Barão de Mauá. It´s adopted as base of methodologic sustentation the Pensamento Complexo, as proposed by Edgar Morin, and as techniques of research the ethnographic practical and bibliographic and documental research. The investigation indicates that the Jaguarão river and the International Bridge of Barão de Mauá, in it´s complementary dynamic, and due to the historic and symbolic context of their formation and use related to the cities of Jaguarão e Rio Branco, present the contours of a Brazilian Cultural Landscape, contributing, in this vision, to estimulate the valorization of heritage on a perspective beyond the political boundary.
A análise empreendida nesta pesquisa parte da percepção da necessidade de estudos mais aprofundados em relação às áreas de fronteira brasileiras, no que tange ao turismo, em especial na sua dimensão cultural e simbólica. Além dos desdobramentos políticos e das construções de sentido acerca das fronteiras, acentuados pelo processo de globalização, despontam novas concepções de patrimônio, ampliando seu entendimento e diversificando os instrumentos de proteção. No presente caso, o estudo centra-se na nova categoria de bem patrimonial Paisagem Cultural Brasileira, que enfatiza a inter-relação e interdependência mútua da ação humana e das características físicas do espaço na configuração especifica de determinada paisagem. Nesses termos, esta investigação apresenta como principal objetivo analisar a possibilidade da nova proposta de bem patrimonial Paisagem Cultural Brasileira dar conta da complexidade da condição limítrofe que permeia os relacionamentos que se processam nos espaços de fronteira, especificamente na fronteira entre Brasil e Uruguai. A investigação se desenvolve nas cidades de Jaguarão (Estado do Rio Grande do Sul, Brasil) e Rio Branco (Departamento de Cerro Largo, Uruguai), buscando compreender a dimensão cultural em um espaço ambíguo de separação-contato condicionado pelo rio Jaguarão e pela Ponte Internacional Barão de Mauá. Adota-se como base de sustentação metodológica o Pensamento Complexo, conforme proposto por Edgar Morin, e como técnicas de pesquisa a prática etnográfica e a pesquisa bibliográfica e documental. A investigação indica que tanto o rio Jaguarão quanto a Ponte Internacional Barão de Mauá, em sua dinâmica de complementaridade, articulam a condição fronteiriça física e simbolicamente, bem como os múltiplos limites que se estabelecem entre os sujeitos de Jaguarão e Rio Branco, delineando contornos que os aproximam da ótica da nova categoria de bem patrimonial nacional, Paisagem Cultural, e contribuindo, nessa ótica, para o estímulo à valorização do patrimônio em uma perspectiva transfronteiriça.
Keywords: TURISMO; Turismo; Fronteira; Paisagem cultural; Jaguarão/RS/Brasil; Rio Branco/Departamento de Cerro Largo/Uruguai; Tourism; Border; Cultural landscape; Jaguarão/RS/Brazil; Rio Branco/Department of Cerro Largo/Uruguay